Transcriptional Analysis of the Human IgE-Expressing Plasma Cell Differentiation Pathway - Ramadani, Faruk; Bowen, Holly; Gould, Hannah J.; Fear, David J. (Frontiers in Immunology, 2019)
IgE is secreted by plasma cells (PCs) and is central to allergic disease. Using an ex vivo tonsil B cell culture system, which mimics the Th2 responses in vivo, we have recently characterized the development pathway of human IgE-expressing PCs. In this system, as in mice, we reported the predisposition of IgE-expressing B cells to differentiate into PCs. To gain a comprehensive understanding of the molecular events involved in the differentiation of human IgE+ B cells into PCs we have used the Illumina HumanHT-12 v4 Expression BeadChip array to analyse the gene expression profile of ex vivo generated human IgE+ B cells at various stages of their differentiation into PCs. We also compared the transcription profiles of IgE+ and IgG1+ cells to discover isotype-specific patterns. Comparisons of IgE+ and IgG1+ cell transcriptional profiles revealed molecular signatures specific for IgE+ cells, which diverge from their IgG1+ cell counterparts upon differentiation into PCs. At the germinal center (GC) stage of development, unlike in some mouse studies of IgE biology, we observed similar rates of apoptosis and no significant differences in the expression of apoptosis-associated genes between the IgE+ and IgG1+ B cells. We identified a gene interaction network associated with early growth response 1 (EGR1) that, together with the up-regulated IRF4, may account for the predisposition of IgE+ B cells to differentiate into PCs. However, despite their swifter rates of PC differentiation, the transcription profile of IgE+ PCs is more closely related to IgE+ and IgG1+ plasmablasts (PBs) than to IgG1+ PCs, suggesting that the terminal differentiation of IgE+ cells is impeded. We also show that IgE+ PCs have increased levels of apoptosis suggesting that the IgE+ PCs generated in our in vitro tonsil B cell cultures, as in mice, are short-lived. We identified gene regulatory networks as well as cell cycle and apoptosis signatures that may explain the diverging PC differentiation programme of these cells. Overall, our study provides a detailed analysis of the transcriptional pathways underlying the differentiation of human IgE-expressing B cells and points to molecular signatures that regulate IgE+ PC differentiation and function.